2012
DOI: 10.1158/1078-0432.ccr-11-2318
|View full text |Cite
|
Sign up to set email alerts
|

Gender Influences the Class III and V β-Tubulin Ability to Predict Poor Outcome in Colorectal Cancer

Abstract: Purpose: Colorectal cancer is one of the deadliest diseases in Western countries. To predict the outcome of therapy, we assessed the role of class III (TUBB3) and class V b-tubulin (TUBB6) as predictive biomarkers.Experimental Design: Using immunohistochemistry and nanofluidics, the expression of TUBB3 and TUBB6 was assessed in two cohorts of 180 and 134 patients, respectively. The CYP17A1 RS743572 was genotyped to identify GG carriers with enhanced androgen levels. TUBB3 and TUBB6 were investigated in 22 colo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 29 publications
(37 reference statements)
4
38
0
Order By: Relevance
“…Although Chung and colleague’s report suggested that the lncRNA PRNCR1 was associated with prostate carcinogenesis and may play a role through the regulation of androgen receptor (AR) transactivation activity [19], no report investigated the relationship between the region 2 of 8q24 and CRC risk. Moreover, there were reports suggested that AR also participated in the pathologic process of CRC through TGFβ pathway [60,61]. In this study, we found that the rs1456315 was also associated with clinical features of CRC, which was consistent with the report by Chung et al [19].…”
Section: Discussionsupporting
confidence: 92%
“…Although Chung and colleague’s report suggested that the lncRNA PRNCR1 was associated with prostate carcinogenesis and may play a role through the regulation of androgen receptor (AR) transactivation activity [19], no report investigated the relationship between the region 2 of 8q24 and CRC risk. Moreover, there were reports suggested that AR also participated in the pathologic process of CRC through TGFβ pathway [60,61]. In this study, we found that the rs1456315 was also associated with clinical features of CRC, which was consistent with the report by Chung et al [19].…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, we have shown that AR knockdown sensitizes bladder cancer cells to doxorubicin (Shiota et al 2012). In addition, AR signaling may be involved in cellular resistance to taxanes including paclitaxel, docetaxel, and cabazitaxel which are key cytotoxic anticancer drugs for prostate cancer, as androgen regulates the expression of the taxane resistance-promoting factor bIII-tubulin (Butler et al 2001, Mariani et al 2012. In fact, CRPC cells in which AR was overexpressed developed cross-resistance to taxanes (Kosaka et al 2011).…”
Section: Pro-survival and Anti-apoptotic Roles Of Ar Signaling In Promentioning
confidence: 94%
“…13 Recently, it has been reported that β III-tubulin expression may predict poor outcome in colorectal cancer, dependent on gender. 14 …”
Section: Introductionmentioning
confidence: 99%